Printing the Qur'an in West Java: Authority, Standardization, and the Making of a Religious Text from Colonial Rule to Reformasi - Muhamad Khabib Imdad; Eni Zulaiha; Jajang A. Rohmana (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Studies on the history of Qur'anic printing in Indonesia have largely focused on codicology, philology, and the standardization of the muṣḥaf, while the historical development of the Qur'anic printing industry at the regional level has received comparatively little scholarly attention. This article examines the historical development of Qur'anic printing in West Java from the pre-independence period to the Reformasi era, with particular attention to the transformation of religious authority, publishing industry, and state standardization. This research employs a qualitative method using a historical approach. Primary data consist of printed Qur’ans published by various publishers in West Java across different historical periods, while secondary data comprise scholarly literature, institutional documents, publishers’ catalogs, and archival materials related to Qur’anic publication and authentication. Data were collected through library research, direct observation of Qur'anic printed editions published in West Java across different historical periods, and documentary analysis. The findings were interpreted through the perspectives of social history and intellectual history. The study demonstrates that the development of Qur'anic printing in West Java evolved through four major typological phases: the initiation of local Qur'anic printing during the pre-independence period led by Maktabah al-Miṣriyyah of Abdullah bin Afif; the institutionalization of the publishing industry during the early post-independence era; the state-led standardization following the implementation of the Indonesian Standard Muṣḥaf during the New Order; and the diversification of the industry during the Reformasi period through product innovation and market segmentation. The study concludes that the history of Qur'anic printing in West Java reflects not only technological developments in Qur'anic reproduction but also broader social transformations and intellectual shifts in religious authority, publishing institutions, and state regulation. It further proposes a typology of Qur'anic printing development that contributes to the broader scholarship on the history of the Qur'anic book in Indonesia